This Sporting Life 1878-1991. - Sarah Campbell Blaffer Gallery, University of Houston, Houston; de Saisset Museum, Santa Clara University, Santa Clara; Delaware Art Museum, Wilmington; Albright-Knox Art Gallery, Buffalo (Atlanta : The High Museum of Art, 1992)
Klucis, Gustav ; Zimmerman, JOhn G. ; Baldessari, John ; Mandel, Mike ; Hockney, David ; Gordon, Jerry ; Barney, Tina ; Epstein, Mitch ; Novak, Lorie ; Pindell, Howardena ; Beck, Robert ; Iooss, Walter Jr. ; Meyerowitz, Joel ; Hamilton, Chris ; Shore, Stephen ; Dow, Jim ; Sternfeld, Joel ; Sultan, Larry ; Koons, Jeff ; Nicosia, Nic ; Staller, Jan ; Leibovitz, Annie ; James, Christopher ; Misrach, Richard ; Graham, David ; etc.
This Sporting Life 1878-1991, The High Museum of Art, Atlanta, Georgia, 16 May - 13 September 1992 ; Sarah Campbell Blaffer Gallery, University of Houston, Texas, 1 November - 16 December 1992 ; de Saisset Museum, Santa Clara University, Santa Clara, California, 12 January - 21 March 1993 ; Delaware Art Museum, Wilmington, Delaware, 16 April - 13 June 1993 ; Albright-Knox Art Gallery, Buffalo, New York, 25 June - 29 August 1993
boek